Combination of intra-operative freehand SPECT imaging with MR images for guidance and navigation - Matthies, Philipp; Okur, Asli; Wendler, Thomas; Navab, Nassir; Friebe, Michael (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2013)
Nowadays for clinical applications such as sentinel lymph node biopsy in breast or prostate cancer, only pre-operative image data is used for navigation, i.e. CT, SPECT/CT or PET/CT. Freehand SPECT and freehand PET provide intra-operative functional imaging techniques that can be complemented with pre- and intra-operative MR imaging to allow for better planning, navigation and guidance. In this paper we propose a method to enable navigation based on pre- or intra-operatively acquired MR images. A fully MR compatible phantom and a dedicated MR compatible optical tracking target with MR markers is built for this study. PET/MR, SPECT/CT and freehand SPECT scans of the phantom are performed. Registration is done using point based registration of the known marker and target geometries and a ground truth is obtained from a SPECT/CT and an MR image that are directly registered. The RMS errors was 0.31mm for the ground truth and 3.29mm when using segmentation of the MR markers and their spatial relationship with the optical tracking spheres of the dedicated target. Thus, the freehand SPECT can be registered easily by this approach without the need of any additional CT scans and therefore without any additional radiation dose for the patient. This enables intra-operative fusion of the pre- or intra-operatively acquired MR data, which could provide valuable additional information for intra-operative applications such as guidance based on accurate anatomy or verifying exact tumor location in combination with detailed morphological patient data. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-08